60.5k views
1 vote
(w-2) (w+5)
I need help I don't understand ...

User Fauzan
by
5.1k points

2 Answers

2 votes
(w-2) (w+5)
w^2 + 5w - 2w - 10
w^2 + 3w - 10
3 votes

Answer: w^2 + 3w - 10

===============================================

Work Shown:

Let x = w-2

This will allow us to replace the (w-2) with x to get...

(w-2)(w+5)

x(w+5)

x*w + x*5 ... distribute

w(x) + 5(x)

Now replace x with w-2 and distribute again

w(x) + 5(x)

w(w-2) + 5(w-2)

w*w + w*(-2) + 5*w + 5*(-2)

w^2 - 2w + 5w - 10

w^2 + 3w - 10

User Weeo
by
4.6k points